Measurement of Anticoagulation in Patients on Dabigatran, Rivaroxaban, and Apixaban Therapy by Novel Automated Thrombelastography - Artang, Ramin; Dias, Joao D.; Walsh, Mark; Bliden, Kevin; Nielsen, Jorn D.; Anderson, Maren; Thurston, Brian C.; Tantry, Udaya S.; Hartmann, Jan; Gurbel, Paul A. (TH Open, 2021)
Background Direct-acting oral anticoagulants (DOACs) do not require monitoring. Measurement of DOAC effect would be useful in the event of bleeding, trauma, and thromboembolism while on anticoagulation. We evaluated the effectiveness of the investigational DOAC assays on the TEG®6s Hemostasis Analyzer to assess the anticoagulant effect of DOACs in patients treated for atrial fibrillation or deep vein thrombosis (DVT).Methods Patients on treatment for a minimum of 7 days with standard doses of dabigatran, rivaroxaban, and apixaban were included. DOAC plasma concentrations and TEG®6s Reaction (R)-time were measured and correlated. The sensitivity, specificity, and negative predictive value (NPV) of R-time to detect DOAC concentrations of ≥30, ≥50, and ≥100 ng/mL were calculated.Results A total of 189 patients were included, (n = 50) on apixaban, (n = 62) on rivaroxaban, (n = 53) on dabigatran, and (n = 24) on no DOAC were studied. Using the direct thrombin inhibitor (DTI) channel, R-time demonstrated strong linear correlation with dabigatran levels (r = 0.93, p < 0.0001). Using the antifactor Xa (AFXa) channel, R-time demonstrated strong nonlinear correlation with rivaroxaban and apixaban levels (rs = 0.92 and 0.84, respectively, p < 0.0001 for both). R-time revealed strong sensitivity and NPV in detecting low DOAC levels for the predefined concentrations.Conclusion R-time measured by TEG®6s DOAC-specific cartridge has a strong correlation with concentrations of the most commonly used DOACs with high sensitivity and NPV for detecting lower drug levels that are considered clinically relevant for patients in need of antidote, or prior to urgent surgery. Further studies to determine the relation of R-time to clinical outcomes are warranted.
Keywords: clinical trials: oral anticoagulants; coagulation inhibitors; diagnosis management; apixaban; rivaroxaban; dabigatran